The Interrelation between Cortical Bone Thickness and Primary and Secondary Dental Implant Stability: a Systematic Review - Halah Al-Juboori; Zygimantas Petronis; Dainius Razukevicius (eJournal of Oral Maxillofacial Research)
Objectives: Dental implants have emerged as a reliable and long-lasting solution for missing teeth, offering advantages over traditional prosthetic options. The aim of this systematic review was to thoroughly explore the correlation between cortical bone thickness of the jaws and bone-level dental implant primary and secondary stability.